Significance of Social Capital in Community Resilience and Performance of Food Security Project in Loima Sub-County, Turkana County, Kenya - Ekiru , Mark; Mulwa, Dr. Angeline Sabina; Kyalo , Prof. Dorothy Ndunge (Advances in Social Sciences Research Journal, 2020)
This paper examines the influence of social capital on performance of food security projects in pastoral livelihood system. This study used semi-structured questionnaires, interview guides and observation check lists to gather data and information. A total of 491 households were sampled across 11 sub-locations. The study findings showed that social capital has a positive influence (r² = 0.2055), however, the correlation varies depending on the type of social capital. This implied that social capital explained 20.55% of the variations in performance of food security projects while the other percentage (79.45%) is explained by other variables which were not included for this study. In terms of comparison, bridging had the strongest influence (r=0.496), followed by linking (r=0.142) then bonding (r=0.102). The overall F statistic of F = 37.12 (p=0.05) was statistically significant since at (p = 0.000 < 0.05) hence was suitable to analyze the relationship between social capital and performance of food security projects. The study found out that bonding and bridging social capital were strong while linking social capital was weak in the community. The study concluded that strong bonding and bridging social capital were limited to enhancing short term absorptive and to less extend adaptive capacity of community while the weak linking capital in the study area was associated with low external engagement coupled with lack of resources and increased number of poor people hence impending long-term resilience building to food insecurity.